Alternative Methods for Resolving Inheritance Disputes Involving a Missing Person (Mafqud) - Ahmad Habib Dairobi; Mhd Yadi Harahap; Abd. Mukhsin (MISYKAT AL-ANWAR JURNAL KAJIAN ISLAM DAN MASYARAKAT, 2026)
The issue mafqud in Islamic inheritance law creates legal uncertainty because it is impossible to determine whether the missing person is alive or deceased. The existence of a mafqud affects the postponement of inheritance distribution and potentially causes disputes among heirs. This study aims to analyze the concept of mafqud in Islamic law and examine the settlement of inheritance disputes involving missing persons within the Religious Courts. This research employs normative legal research using statutory and conceptual approaches. The legal materials consist of primary, secondary, and tertiary legal sources analyzed through qualitative descriptive methods. The results indicate that a mafqud is a person whose whereabouts are unknown and whose legal status remains uncertain. Under Islamic law, a mafqud is presumed alive based on the doctrine of istishab until evidence of death is established. The settlement of inheritance disputes involving a mafqud in Religious Courts is conducted through judicial determination by considering evidence, the period of disappearance, circumstances surrounding the disappearance, and principles of public benefit and legal certainty. Such determination seeks to protect the rights of the missing person while ensuring legal certainty for the remaining heirs.